Design Engineering 2002
DOI: 10.1115/imece2002-33200
|View full text |Cite
|
Sign up to set email alerts
|

FEA Rotating Tire Modeling for Transient Response Simulations

Abstract: A full nonlinear finite element P185/70R14 passenger car radial-ply tire model was developed and run on a 1.7-meter-diameter spinning test drum. The virtual tire/drum/cleat finite element model was constructed and tested using the nonlinear finite element analysis software, PAM-SHOCK. The tire model was constructed in extreme detail with three-dimensional solid, layered membrane, and beam finite elements, incorporating over 18,000 nodes and 24 different types of materials. In addition to the tire model itself,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The determination of the tire in-plane free vibration modes was achieved by recording the reaction force of the tire axle at longitudinal and vertical directions when the tire rolling over a cleat on the road. The results were compared to more than ten previous studies and showed good agreement [6].…”
Section: Fig 1 Common Approaches Used To Study the Mechanics Of Wheementioning
confidence: 66%
See 1 more Smart Citation
“…The determination of the tire in-plane free vibration modes was achieved by recording the reaction force of the tire axle at longitudinal and vertical directions when the tire rolling over a cleat on the road. The results were compared to more than ten previous studies and showed good agreement [6].…”
Section: Fig 1 Common Approaches Used To Study the Mechanics Of Wheementioning
confidence: 66%
“…The second peak at approximately 46 Hz corresponds to the first vertical free vibration mode. The available experimental data for the first vertical free vibration mode for passenger cars tires lies in the range of 60-80 Hz [16].For the developed FEA off-road tire which has larger diameter and softer materials comparing to passenger car tires, its sidewalls will absorb more vibrations instead of transferring it to the tire center. So, it can be expected to have values lower than 60 Hz.…”
Section: First Mode Of Vibration Testmentioning
confidence: 99%
“…C 10 and C 01 are the first (loading) and second (loading) Mooney-Rivlin law coefficients, respectively. Further details regarding the material selection and parameter identification can be found in the previous publication [28].…”
Section: Tire Materials Definitionmentioning
confidence: 99%